Fibroblast growth factor receptors and ligands in context of bevacizumab response in ovarian carcinoma: an exploratory analysis of AGO-OVAR11/ICON-7 - Heublein, Sabine; Pfisterer, Jacobus; du Bois, Andreas; Anglesio, Michael; Aminossadati, Behnaz; Bhatti, Irfan A.; Sehouli, Jalid; Wimberger, Pauline; Schochter, Fabienne; Hilpert, Felix; Hillemanns, Peter; Kalder, Matthias; et al. (Laboratory investigation, 2024)
With more novel drugs being approved for the treatment of ovarian carcinoma, the question remains to what extent patients benefit from antiangiogenic treatment with bevacizumab, either in combination with poly-(ADP-ribose) polymerase inhibitors or as single-agent maintenance. As fibroblast growth factor receptors and their ligands (FGFRs/FGFs) are key players in angiogenic signaling and have been linked to resistance to several drugs, we investigated the prognostic or predictive potential of FGFs/FGFRs signaling in the context of bevacizumab treatment within the prospective phase III AGO-OVAR11/ICON-7 study. FGFR1, FGFR2, FGFR3, FGFR4, FGF1, and FGF19 gene expressions were determined in 380 ovarian carcinoma tumor samples collected from German centers in the multicenter phase III AGO-OVAR11 trial/ICON-7 trial. All patients received carboplatin and paclitaxel, administered every 3 weeks for 6 cycles, and were randomized to bevacizumab. Expressions of FGFR1, FGFR2, FGF1, and FGF19 were associated with progression-free survival in both uni- and multivariate (FGFR1: HR, 1.6, P < .001; FGFR2: HR, 1.6, P = .002; FGF1: HR, 2.3, P < .001; and FGF19: HR, 0.7; P = .007) analysis. A signature built by FGFR1, FGFR4, and FGF19 defined a subgroup (n = 62) of patients that derived the greatest bevacizumab-associated improvement of progression-free survival (HR, 0.3; P = .004). In this exploratory analysis of a prospective randomized phase III trial, we provide evidence that the expression of FGFRs/FGFs might have independent prognostic values. An FGFR/FGF-based gene signature identified in our study appears to predict long-term benefit from bevacizumab. This observation is hypothesis-generating and requires validation on independent cohorts.